TRANSFORMASI REGULASI PENANAMAN MODAL: IMPLIKASI PERPRES NOMOR 10 TAHUN 2021 TERHADAP SEKTOR INDUSTRI - Padhilah, Piqi Rizki; Sugiarti, Lilis Diah; Yusup, Deni Kamaludin (Jurnal Ilmiah Dinamika Hukum, 2026)
Presidential Regulation Number 10 of 2021 on Investment Business Fields introduces a fundamental transformation in Indonesia’s investment regulatory regime by replacing the previous negative list approach with a positive list system. This regulatory shift significantly affects the structure of investment liberalization, particularly in the industrial sector, which serves as the backbone of the national economy. This study aims to analyze the regulatory changes introduced by Presidential Regulation 10/2021 and examine their juridical and practical implications for the investment climate and industrial business actors. Using a normative juridical method through the analysis of legislation, policy documents, and academic literature, this research finds that the regulation enhances investment openness, expands foreign ownership, simplifies risk-based licensing, and strengthens legal certainty through the classification of priority business fields, mandatory partnerships with cooperatives/MSMEs, and conditioned business categories. However, its implementation still faces challenges, including the harmonization of sectoral regulations, regulatory–political dynamics, and the government’s supervisory capacity. Overall, Presidential Regulation 10/2021 has the potential to strengthen the attractiveness of the industrial sector and its integration into global value chains, yet its effectiveness strongly depends on consistent implementation and cross-sector policy alignment. Keywords: Presidential Regulation 10/2021, investment regulation, investment liberalization, industrial sector, investment policy.